2017
DOI: 10.1038/nrneurol.2017.129
|View full text |Cite|
|
Sign up to set email alerts
|

PET imaging of the neurovascular interface in cerebrovascular disease

Abstract: Cerebrovascular disease encompasses a range of pathologies that affect different components of the cerebral vasculature and brain parenchyma. Large artery atherosclerosis, acute cerebral ischaemia, and intracerebral small vessel disease all demonstrate altered metabolic processes that are key to their pathogenesis. Although structural imaging techniques such as MRI are the mainstay of clinical care and research in cerebrovascular disease, they have limited ability to detect these pathophysiological processes i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 149 publications
0
24
0
Order By: Relevance
“…41 Variable resolution acquisitions in healthy human subjects showed cardiac structure and neuro-vasculature in the pyruvate data set that would otherwise be missed due to partial-volume effects and illustrates the level of detail that can be achieved with hyperpolarized substrates in a clinical setting, approaching that of 1 H MRSI and some positron emission tomography (PET) radiotracers. [42][43][44][45] A variable resolution approach would also be beneficial when the biodistribution of metabolites is the primary interest 34 or when performing co-polarization studies with inert perfusion agents, such as 13 C urea, 46 and would provide an opportunity to acquire F I G U R E 6 AUC images from a healthy cardiac volunteer. The pyruvate data, acquired at finer resolution, provides improved contrast between the left and right ventricles and the myocardium and papillary muscles.…”
Section: Discussionmentioning
confidence: 99%
“…41 Variable resolution acquisitions in healthy human subjects showed cardiac structure and neuro-vasculature in the pyruvate data set that would otherwise be missed due to partial-volume effects and illustrates the level of detail that can be achieved with hyperpolarized substrates in a clinical setting, approaching that of 1 H MRSI and some positron emission tomography (PET) radiotracers. [42][43][44][45] A variable resolution approach would also be beneficial when the biodistribution of metabolites is the primary interest 34 or when performing co-polarization studies with inert perfusion agents, such as 13 C urea, 46 and would provide an opportunity to acquire F I G U R E 6 AUC images from a healthy cardiac volunteer. The pyruvate data, acquired at finer resolution, provides improved contrast between the left and right ventricles and the myocardium and papillary muscles.…”
Section: Discussionmentioning
confidence: 99%
“…PET scans operate on the principle that positron-emitting radioligands accumulate in a region of interest. The positively-charged positrons encounter negatively-charged electrons, which results in annihilation releasing gamma photons that are detected by scintillation detectors [ 16 ]. This method can be used to image Aβ in vivo via radiolabeled tracers, which are injected via a bolus injection, followed by a waiting period to allow for uptake by brain tissue.…”
Section: Imaging Amyloid Burdenmentioning
confidence: 99%
“…[7][8][9][10] In 2017, Li et al 11 demonstrated that CoCl 2 -induced hypoxia promoted cell migration and proliferation in placenta-derived mesenchymal stem cells. [7][8][9][10] In 2017, Li et al 11 demonstrated that CoCl 2 -induced hypoxia promoted cell migration and proliferation in placenta-derived mesenchymal stem cells.…”
mentioning
confidence: 99%